2019
DOI: 10.1089/cap.2018.0119
|View full text |Cite
|
Sign up to set email alerts
|

Attendance and Engagement in Parent Training Predict Child Behavioral Outcomes in Children Pharmacologically Treated for Attention-Deficit/Hyperactivity Disorder and Severe Aggression

Abstract: Objectives: We examined the association of parent training (PT)-related factors with therapeutic success in the Treatment of Severe Childhood Aggression (TOSCA) study. Our aims were (1) to evaluate demographic and clinical characteristics as predictors of parent attendance and engagement in PT and (2) to examine the associations of parent attendance and engagement in PT with study-targeted child behavior outcomes (i.e., attention-deficit/hyperactivity disorder [ADHD] and disruptive behavior symptoms). TOSCA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…And only one gender difference (out of five outcomes investigated) emerged that indicated girls benefited more than boys in peer problems after their parents completed the IY Attentive Parenting Program. While some studies suggested no differences in PT attendance among ethnic-racially diverse families (e.g., Dumas et al, 2007), others found ethnic-racial minorities were less likely to attend (e.g., Joseph et al, 2019). The underlying factor beneath the mixed findings with ethnicity and race may be the cultural responsiveness of the PT and the facilitator.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…And only one gender difference (out of five outcomes investigated) emerged that indicated girls benefited more than boys in peer problems after their parents completed the IY Attentive Parenting Program. While some studies suggested no differences in PT attendance among ethnic-racially diverse families (e.g., Dumas et al, 2007), others found ethnic-racial minorities were less likely to attend (e.g., Joseph et al, 2019). The underlying factor beneath the mixed findings with ethnicity and race may be the cultural responsiveness of the PT and the facilitator.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to treatment outcomes, we also evaluated parents' attendance in the IY Attentive Parenting Program. Consistent with prior PT studies (Joseph et al, 2019), we examined whether demographic (e.g., race and gender) and clinical characteristics (e.g., parenting stress and child psycho pathology) would account for parents' attendance in the IY Attentive Parenting Program. Studying the attendance rate in an implementation study is crucial to understanding the feasibility of PT.…”
Section: Evaluation Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study, which examined the outcome of behavioral parent training for children and their families, also found that children's ODD symptoms were a significant predictor of attendance. This could be as a result of parents' lack of understanding about skills being taught, or lack of ability to implement these appropriately in conjunction with their children's needs (Joseph et al, 2018). Other studies illustrate that there can, in fact, be a decline among sessions with those families of children who have higher ratings of oppositional defiant disorder.…”
Section: Comorbid Oppositional/defiant Behavior (Odd)mentioning
confidence: 99%